Eksistensi Partai Demokrasi Indonesia Perjuangan dalam Pemilu Legislatif Di Kabupaten Subang Tahun 1999-2014 - Armillah, Helmi Rizqi (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This research begins with the issue of the effect of the Indonesian Democratic Party of Struggle victory in the legislative elections in Subang Regency. Thus, this research focuses on the development of the Indonesian Democratic Party of Struggle in 1999 until 2014 in Subang Regency. This study aims to identify political programs, strategies and the impact of the Indonesian Democratic Party of Struggle in Subang Regency. The method used by researcher is historical method with a multidisciplinary approach. The finding of this research is the development of Indonesian Democratic Party of Struggle in Subang Regency experienced the same thing as happened at the national level by dividing two camps within the Indonesian Democratic Party body and fighting over the secretariat office, which in the end was won by the Indonesian Democratic Party of Struggle in 2002.  Indonesian Democratic Party of Struggle in Subang Regency had programs aimed at commoners or the underprivileged. At the beginning of the development, the Indonesian Democratic Party of Struggle in Subang Regency programs were carried out by internal party programs. The next period began to develop programs aimed at the fields of economic field, social, and politic. Indonesian Democratic Party of Struggle’s strategies in the victory of legislative elections is mostly carried out in various ways namely staying firm on party ideology, the presence of Bung Karno and Megawati figures as figures who have influence in the party and in its campaign. The cadres Indonesian Democratic Party of Struggle has a close relationship with the community and directly involved with the community in developing the Subang Regency region, selecting and mapping the legislative candidates appropriately in each chosen region. Indonesian Democratic Party of Struggle in Subang Regency succeeded in making its cadres in important positions in the Subang Regency Government as the Regent and Deputy Regent, as well as the chairman of the Subang Regency Assembly at reginal for four periods namely 1999-2014.